Diseases presenting with vesicular and erosive lesions of oral mucous membranes - Kamila Ociepa (Przegląd Dermatologiczny, 2017)
Disorders of the oral mucosa are an area of interdisciplinary cooperation involving physicians from a diverse range of medical specialties. Diseases characterized by a similar mucosal abnormalities include lichen planus, pemphigus vulgaris, paraneoplastic pemphigus, mucous membrane pemphigoid, epidermolysis bullosa acquisita, linear IgA bullous dermatosis and chronic ulcerative stomatitis.